Management of Bee Sting Induced Anaphylaxis and Acute Kidney Injury in a Husky Dog - Sakshi,; Mini, Remya; Dahiya, Ankit; Karunanithy, Mahendran; Rana, Manjali; Kumar , Ujjwal (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Apidae (bees), Vespidae (hornets, wasps, and yellow  jackets), and Formicidae (fire ants) the three genera of  Hymenoptera are most responsible for physical symptoms  associated with allergic reactions seen in veterinary facilities  (Casale and Burks, 2014). The venom in the sting can  produce conditions ranging from minor local lesions to life threatening systemic reactions. It is worth mentioning here  that the honeybees can only sting once in their lifetime as  their barbed stinger snags in the victim’s skin, ripping the  stinging mechanism from the bee’s body and killing the  bee. The venom sac keeps contracting outside the body of  the bee, and 100% of its venom is delivered over 60 seconds.  Honeybee venom is a clear acidic substance consisting  of several enzymes, proteins, and amines that can cause  poisonous and adverse reactions in the bodies of those  who are exposed to it. Melittin and phospholipase A2 are  the primary components of bee venom, however several  additional chemicals are also present. These compounds cause  haemolysis, rhabdomyolysis, renal tubule degradation, and  necrosis, ultimately leading to failure of the organs (Almeida  et al., 2011). Melittin, in collaboration with phospholipase  A2, breaks cell membranes in certain mammals, resulting  in lysis of erythrocytes, leukocytes, platelets, myocytes,  and vascular endothelium. Hyaluronidase, often known as  “spreading factor” in venom, is responsible for modifying  the permeability of cell membranes and thus allowing other  venom components to permeate into the tissues of the host.  Melittin has the potential to adhere to and generate transitory  holes on the surface of red blood cells, which can range from  minor to severe depending on weather conditions, age, and  the types of flowers used by bees for honey production. The  deadly dose for humans and mammals is believed to be 500  stings per adult and 20 stings per kilogram, respectively  (Vetter et al., 1999). Intravascular haemolysis, rhabdomyolysis,  hepatopathy, cardiac injury, acute kidney injury,  immune mediated haemolytic anaemia (IMHA), immune-mediated  thrombocytopenia (IMTP), and disseminative intravascular  coagulopathy (DIC) are all side consequences of severe  envenomation and anaphylaxis. This document reports  successful management of bee sting induced anaphylaxis  and acute kidney injury in a Husky dog.
Keywords: Apidae (bees); Formicidae; erythrocytes; leukocytes